PRASANGKA ANTAR ETNIS SISWA KELAS VIII A SEKOLAH MENENGAH PERTAMA NEGERI 3 SUNGAI RAYA - Wani, Nur Aisyah; Zakso, Amrazi; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The title of this study is: Inter-Ethnic Prejudice of Class A Students at The State of Junior High School 3 Sungai Raya. A common problem of this research was the Prejudice Inter-Ethnic of The Students at The State of Junior High School 3 Sungai Raya. The scope of this research includes stereotypical of inter-ethnic in stereotypes, social distance and discrimination of inter-ethnic of the students at The State of Junior High School 3 Sungai Raya. The qualitative approach was used in this research study. The technique of data collecting by using observation, interview and documentation study with tool of data collection by using observation guide, interview guide, note book and archives. The results of this study indicated that stereotypes inter-ethnic, the social distance inter-ethnic and the discrimination of Class A Students at The State of Junior High School 3 Sungai Raya are very minimal. In this study, it is not ethnic issues that make them prejudiced towards certain people, but the problem comes from individual of the students. Keywords : Prejudice, Ethnic,Students Keberagaman tidak jarang menimbulkan gesekan dalam masyarakat berupa prejudice (prasangka). Prejudice (prasangka) menurut Horton dan Hunt (1999: 65) merupakan â€œSuatu penilaian yang dinyatakan sebelum mengetahui segenap fakta, yakni sikap etnosentrisme yang cenderung membuat kita menganggap baik orang-orang dalam kelompok sendiri dan menganggap buruk orangorang diluar kelompok kita. Prasangka dapat merusak penilaian kita dan membuat kita tidak mampu mencapai keputusan yang rasionalâ€. Oleh karena itu, jika seseorang berada dalam lingkungan kelompok etnis yang berbeda, maka cenderung untuk bersikap stereotip dan diskriminasi tehadap kelompok etnis lain. Menurut Paul B. Horton dan Chester L. Hunt (1999: 65) â€œJika orang ditugaskan pada beberapa kelompok